Epoxyeicosatrienoic acids attenuating hypotonic-induced apoptosis of IMCD cells via γ-ENaC inhibition. - Luyun Wang; Yang Liu; Huamin Wang; Xun Liu; Jie Chen; Mong-Heng Wang; Jingfeng Wang; Hui Huang (PLoS ONE)
Inner medulla collecting duct (IMCD) cells are the key part for urinary concentration. Hypotonic stress may trigger apoptosis of IMCD cells and induce renal injury. Epoxyeicosatrienoic acids (EETs) play an important role in anti-apoptosis, but their roles in hypotonic-induced apoptosis of IMCD cells are still unclear. Here we found increasing exogenous 11, 12-EET or endogenous EETs with Ad-CMV-CYP2C23-EGFP transfection decreased apoptosis of IMCD cells induced by hypotonic stress. Moreover, up-regulation of γ-ENaC induced by hypotonic stress was abolished by elevation of exogenous or endogenous EETs. Collectively, this study illustrated that EETs attenuated hypotonic-induced apoptosis of IMCD cells, and that regulation of γ-ENAC may be a possible mechanism contributing to the anti-apoptotic effect of EETs in response to hypotonic stress.